“Your Next Stay Will Be on Us”: Genre Analysis of Hotel Responses to Negative Reviews - Cita Nuary Ishak (English Learning Innovation (englie), 2022)
The purpose of the present paper is to identify the typical moves, steps, and common expressions in hotels’ responses to negative reviews (RNRs) posted on TripAdvisor. A specialized corpus comprising authentic 29 responses, written by top seven 4- and 5-star hotels in Malang was explored by following Swales’ notion of move analysis. Corpus-assisted analysis was also applied to identify some frequent expressions typical to major moves. The findings revealed that the generic structure of RNRs written by top hotels in Malang contain six moves and 23 steps. Unique to this finding are four additional steps that were distinct from previous studies, but appeared in the corpus: appreciating the stay, promoting hotel’s facility, clarifying misunderstanding, and making amends. ‘Thank you for’ (appearing 30 times in 22 responses) were among the most frequent expressions in major moves such as appreciating the stay and expressing gratitude. Other common expressions were also identified from the corpus and used as the basis of proposing a brief guideline for composing RNRs, which can be useful for teaching business English, or English for Specific Purposes. Overall, these findings outline a generic pattern through which representatives of top hotels in Malang manage customers’ dissatisfactions and complaints. Since these findings were derived from natural-occurring data, they can also be useful to classroom instructions, especially in providing authentic materials.